2020
DOI: 10.1177/2048872619899309
|View full text |Cite
|
Sign up to set email alerts
|

Impact of previous coronary artery bypass grafting in patients presenting with an acute coronary syndrome: Current trends and clinical implications

Abstract: Background: Among patients presenting with an acute coronary syndrome, those with previous coronary artery bypass grafting are a particular subset. Aims: The purpose of this study was to investigate the prognostic impact of previous coronary artery bypass grafting in acute coronary syndrome patients and to identify the current trends in their clinical management. Methods: We performed a cohort analysis of patients prospectively enrolled in the Portuguese Registry of acute coronary syndrome between 2010–2019 wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…[17][18][19][20] Although there is an evidence gap in the management of ACS in patients with prior CABG, PCI rates in this group has been consistently lower compared with patients without prior CABG. 2,4,14,[21][22] Patients with prior CABG in our study were significantly less likely to be referred for surgical revascularisation, likely due to older age, more complex coronary anatomy and higher risk profile. Previous studies have demonstrated higher mortality risk with repeat CABG when compared with medical management and revascularisation with PCI.…”
Section: Myocardial Revascularisationmentioning
confidence: 76%
See 3 more Smart Citations
“…[17][18][19][20] Although there is an evidence gap in the management of ACS in patients with prior CABG, PCI rates in this group has been consistently lower compared with patients without prior CABG. 2,4,14,[21][22] Patients with prior CABG in our study were significantly less likely to be referred for surgical revascularisation, likely due to older age, more complex coronary anatomy and higher risk profile. Previous studies have demonstrated higher mortality risk with repeat CABG when compared with medical management and revascularisation with PCI.…”
Section: Myocardial Revascularisationmentioning
confidence: 76%
“…1 Several studies have also demonstrated similar findings. 2,[4][5][6]14 Prior CABG patients are more likely to present with UA and less likely to present with STEMI. A possible explanation is the formation of coronary arterial collaterals resulting in a smaller infarct size.…”
Section: Baseline Characteristics and Coronary Angiography Accessmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent observational studies dedicated to LF-LG AS patients have outlined favorable early outcomes following TAVI [ 36 ] with lower 30-day mortality rates compared to those reported in prior TAVI studies evaluating LF-LG AS patients [ 31 , 37 ] as well as SAVR studies in LF-LG AS, despite including younger and lower risk patients [ 9 , 10 , 16 , 17 , 37 , 38 , 39 , 40 , 41 , 42 ]. However, despite the good early results post-TAVI in LF-LG AS patients and the constant optimization of the final hemodynamic result achieved with the latest THVs (transcatheter heart valves), the mid-term all-cause mortality remains high with approximately one-third of LF-LG patients dying after a median follow-up of 2-years [ 43 ]. Our study wished to expand on that knowledge and investigate whether this rise in all-cause mortality in LF-LG AS patients persists up to 5-years of follow-up and holds statistical significance over the other subgroups of AS patients.…”
Section: Discussionmentioning
confidence: 99%